2019
DOI: 10.1007/s00038-018-1196-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in suicidal behavior in adolescents and young adults: systematic review and meta-analysis of longitudinal studies

Abstract: Objectives To assess the association between gender and suicide attempt/death and identify gender-specific risk/protective factors in adolescents/young adults. Methods Systematic review (5 databases until January 2017). Population-based longitudinal studies considering non-clinical populations, aged 12–26 years, assessing associations between gender and suicide attempts/death, or evaluating their gender risk/protective factors, were included. Random effect meta-analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

56
337
9
36

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 542 publications
(438 citation statements)
references
References 69 publications
56
337
9
36
Order By: Relevance
“…Fourth, higher suicide rates were reported among males (4.83/100,000 individuals) compared with females (1.95/100,000 individuals) in this age range. This sex effect is consistent with many prior studies in youth (Bridge et al, 2006;Cha et al, 2018;Kõlves & De Leo, 2014McLoughlin et al, 2015;Miranda-Mendizabal et al, 2019;Roh et al, 2018;V€ arnik et al, 2009;Wasserman et al, 2005) and is also found among adults (Bachmann, 2018;Canetto & Sakinofksy, 1998;Chang et al, 2019;Nock, Borges, Bromet, Cha, et al, 2008;Schrijvers et al, 2012). Higher suicide death rates among males have been attributed to a range of factors, including greater use of lethal means (e.g., hanging and use of firearms; Callanan & Davis, 2012) and higher incidence of risk factors related to suicide death, such as substance use and aggressive and risk-taking behaviors (Bozzay, Liu, & Kleiman, 2014).…”
Section: (B) Malessupporting
confidence: 92%
“…Fourth, higher suicide rates were reported among males (4.83/100,000 individuals) compared with females (1.95/100,000 individuals) in this age range. This sex effect is consistent with many prior studies in youth (Bridge et al, 2006;Cha et al, 2018;Kõlves & De Leo, 2014McLoughlin et al, 2015;Miranda-Mendizabal et al, 2019;Roh et al, 2018;V€ arnik et al, 2009;Wasserman et al, 2005) and is also found among adults (Bachmann, 2018;Canetto & Sakinofksy, 1998;Chang et al, 2019;Nock, Borges, Bromet, Cha, et al, 2008;Schrijvers et al, 2012). Higher suicide death rates among males have been attributed to a range of factors, including greater use of lethal means (e.g., hanging and use of firearms; Callanan & Davis, 2012) and higher incidence of risk factors related to suicide death, such as substance use and aggressive and risk-taking behaviors (Bozzay, Liu, & Kleiman, 2014).…”
Section: (B) Malessupporting
confidence: 92%
“…On the other hand, taking into account that a transition from suicide ideation to suicide attempt is very common during adolescence [35], eight out of every hundred adolescents in the sample evaluated can be considered to be at a severe risk of suicide. However, although previous studies have found differences in suicidal behavior by sex, showing females to have a higher risk of suicide attempts and males have a higher risk of suicidal death [36], no differences have emerged in the present study. Similarly, differences in suicidal behavior by age have not been found in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Most of the evidence about STB risk and protective factors come from Anglo‐Saxon countries; Spanish cross‐national data is limited. Moreover, the available evidence of gender‐differences in STB risk and protective factors is not specific for university students (Miranda‐Mendizabal et al, ). This study aims to determine the association between risk and protective factors and STB stratified by gender and to assess whether there is any interaction between those factors and gender with STB among Spanish university students.…”
Section: Introductionmentioning
confidence: 99%